The effect of service quality and location on tourist satisfaction in Denai Lama tourism village, Deli Serdang regency - Kamal, Mustafa (International Journal of Culture and Art Studies, 2025)
This study aims to analyze the influence of service quality and location on tourist satisfaction in Denai Lama Tourism Village, Deli Serdang Regency. The background of this research is based on the importance of sustainable management of community-based tourist destinations in increasing the competitiveness and loyalty of tourists. This study employs a quantitative descriptive approach, utilizing a survey method with 80 tourists who visited Denai Lama Tourism Village. The results of the multiple linear regression analysis showed that the variables of service quality (X₁) and location (X₂) had a significant effect on tourist satisfaction (Y), accounting for 84.2% of the contribution. These findings confirm that friendly, fast, and communicative services, as well as strategic and easily accessible locations, are the dominant factors that affect the level of satisfaction among tourists. This research offers practical implications for tourism village managers to enhance service standards and location governance, thereby maintaining visitor loyalty and ensuring the sustainability of tourist destinations.